ANALISIS PENGGUNAAN BAHASA IBU “SASAK” DALAM MELESTARIKAN BUDAYA LOKAL DI SD NEGERI 2 KELAYU UTARA - Asri Nofita Sari; Andi Sulastri; Hadiatul Rodiyah; Habibuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the use of the mother tongue (Sasak) in preserving local culture at SD Negeri 2 Kelayu Utara. This study uses a descriptive qualitative method with the research subjects being the principal, a sample of teachers from grades 1–6, and 5 samples of students from grades 4 and 5. Data collection techniques used were observation, interviews, and documentation, while data analysis used the Miles and Huberman model, namely collection, reduction, presentation, and drawing conclusions. The results of the study indicate that the use of the mother tongue (Sasak) is still relatively low because the majority of school residents prefer to use Indonesian in daily communication. However, teachers and students sometimes use Sasak spontaneously in certain interactions. One of the supporting factors for the use of the mother tongue is a homogeneous social environment, with the majority of school residents having the same language family, namely the ngeno-ngene dialect. Meanwhile, one of the inhibiting factors includes the habit of using Indonesian, the influence of digital media, and slang. One of the school's efforts to preserve the mother tongue is through a Sasak language program every Thursday before teaching and learning activities begin. This program fostered students' interest in storytelling, storytelling, rhymes, speeches, and singing in the Sasak language. However, the program is currently discontinued due to the school's implementation of the 7 habits of great Indonesian children.